2015
DOI: 10.1051/0004-6361/201424933
|View full text |Cite
|
Sign up to set email alerts
|

VLT X-Shooter spectroscopy of the nearest brown dwarf binary

Abstract: Aims. The aim of the project is to characterise the two components of the brown dwarf system nearest to the Sun, WISE J104915.57−531906.1 (also called Luhman 16AB) at optical and near-infrared wavelengths. Methods. We obtained high signal-to-noise intermediate-resolution (R ∼ 6000−11 000) optical (600−1000 nm) and near-infrared (1000−2480 nm) spectra of each component of Luhman 16AB with the X-Shooter instrument on the Very Large Telescope. Results. We classify the primary and secondary of the Luhman 16 system… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 74 publications
(180 reference statements)
6
37
0
Order By: Relevance
“…Burrows & Sharp 1999;Lodders & Fegley 2006), Li is predicted to be in atomic form above ∼1500-1700 K at 1 bar pressure but converted into molecules at lower temperatures. Hence, we would expect chemical depletion of Li for ultracool dwarfs below 1500 K, which seems supported by observations of the coolest L and T dwarfs (Kirkpatrick et al 2008;King et al 2010;Faherty et al 2014;Lodieu et al 2015).…”
Section: Searches For Lithium In Cooler Subdwarfssupporting
confidence: 69%
See 1 more Smart Citation
“…Burrows & Sharp 1999;Lodders & Fegley 2006), Li is predicted to be in atomic form above ∼1500-1700 K at 1 bar pressure but converted into molecules at lower temperatures. Hence, we would expect chemical depletion of Li for ultracool dwarfs below 1500 K, which seems supported by observations of the coolest L and T dwarfs (Kirkpatrick et al 2008;King et al 2010;Faherty et al 2014;Lodieu et al 2015).…”
Section: Searches For Lithium In Cooler Subdwarfssupporting
confidence: 69%
“…Tinney (1998), Kirkpatrick et al (1999Kirkpatrick et al ( , 2000, Pavlenko et al (2007a), Cruz et al (2009), and Zapatero Osorio et al (2014). In the T dwarf regime, only Luhman 16B is known to harbour Li in absorption with an equivalent width of ∼8 Å (Faherty et al 2014;Lodieu et al 2015) whereas Li is undetected in Gl 229 B (Schultz et al 1998;Oppenheimer et al 1998) and in the two component of Epsilon Indi B (King et al 2010). Lithium remains undetected in the optical spectrum of another 17 T dwarfs (Burgasser et al 2003b;Kirkpatrick et al 2008;Leggett et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, we recall that low-mass stars are predicted to reach effective temperatures > ∼ 2000 K (as estimated using the 10 Gyr Dusty model from , and corresponding to optical spectral types < ∼ L3, using the scale from Kirkpatrick et al 2008) and that the cooler, late-type L, T, and Y dwarfs of the sample are therefore expected to be substellar objects, independent of age (see also Kirkpatrick 2013). The L7.5 and T0.5 components of WISE J1049-5319 in the 6.5 pc sample, for instance, present Li  absorption in their optical spectra and are brown dwarfs Lodieu et al 2015) based on the lithium test (Rebolo et al 1992). Besides, LP 944-20 (M9) is the unique M-type object in the 6.5 pc sample identified as a brown dwarf, also through the lithium test.…”
Section: Data Analysis and Resultsmentioning
confidence: 97%
“…This chemical depletion at low temperatures has not previously been tested with objects of known mass. The latest-type object known to display Li I absorption is WISE J1049−5319B (T0; Faherty et al 2014;Lodieu et al 2015), implying that any of the L dwarfs in our sample might plausibly display Li I absorption if they are not depleted by Li fusion. Figure 9 shows our individual masses as a function of age for the 13 systems with well constrained model-derived ages, i.e., systems containing at least one brown dwarf, as well as the pre-main-sequence binary LP 349-25AB.…”
Section: Lithium Fusion Mass Limitmentioning
confidence: 92%
“…Models from Lodders (1999) indicate that monatomic lithium ceases to be the dominant lithium-bearing species below T eff ≈ 1500 K at pressures near the photosphere (∼1 bar). Detailed spectral synthesis modeling shows that Li I absorption can in fact persist to much lower temperatures (e.g., Pavlenko et al 2000;Allard et al 2001), and indeed it has been detected in objects as cool as WISE J1049−5319B (T0; Faherty et al 2014;Lodieu et al 2015). Kirkpatrick et al (2008) reported strong Li I absorption (EW = 11Å) in the integrated-light spectrum of SDSS J0423−0414AB.…”
Section: B3 Sdss J0423−0414ab (L65+t2)mentioning
confidence: 99%